Effect of dietary l-carnitine supplementation to sows during gestation and/or lactation on sow productivity, muscle maturation and lifetime growth in progeny from large litters. Issue 1 (14th July 2020) - Rooney, Hazel B.; O'Driscoll, K.; Silacci, P.; Bee, G.; O'Doherty, J. V.; Lawlor, P. G.
Abstract: Genetic selection for increased sow prolificacy has resulted in decreased mean piglet birth weight. This study aimed to investigate the effect of l -carnitine (CAR) supplementation to sows during gestation and/or lactation on sow productivity, semitendinosus muscle (STM) maturity and lifetime growth in progeny. Sixty-four sows were randomly assigned to one of the four dietary treatments at breeding until weaning: CONTROL (0 mg CAR/d), GEST (125 mg CAR/d during gestation), LACT (250 mg CAR/d during lactation) and BOTH (125 mg CAR/d during gestation and 250 mg CAR/d during lactation). The total number of piglets born per litter was greater for sows supplemented with CAR during gestation (17·3 v . 15·8 (sem 0·52); P < 0·05). Piglet birth weight (total and live) was unaffected by sow treatment ( P > 0·05). Total myofibre number ( P = 0·08) and the expression level of selected myosin heavy chain genes in the STM ( P < 0·05) were greater in piglets of sows supplemented with CAR during gestation. Pigs from sows supplemented with CAR during gestation had lighter carcasses at slaughter than pigs from non-supplemented sows during gestation (83·8 v . 86·7 (sem 0·86) kg; P < 0·05). In conclusion, CAR supplementation during gestation increased litter size at birth without compromising piglet birth weight. Results also showed that the STM of piglets born to sows supplemented with CAR during gestation was more developed at birth. However, carcass weight at slaughter was reduced in progeny of sows supplemented with CAR during gestation. The CAR supplementation strategy applied during gestation in this study could be utilised by commercial pork producers to increase sow litter size and improve offspring muscle development.